Adsorption of Lead on Lentil Husk in Fixed Bed Column Bioreactor. (July 2019) - Basu, Mousumi; Guha, Arun K.; Ray, Lalitagauri
Graphical abstract: Highlights: Column reactor with lentil husk fixed bed was employed for continuous removal of lead. Design parameters of the reactor had considerable influence on adsorption. Mathematical models well interpreted the experimental outcome. Kinetic study revealed high level of percentage adsorption. The sorbent displayed high adsorption capacities at elevated feed concentrations. Abstract: This study depicts successful employment of fixed bed column bioreactor for adsorption of lead in continuous mode using lentil husk as sorbent. Design parameters considerably controlled the reactor performance, amongst which height of the fixed bed and flow rate were crucial in generating cleaner effluent. Adsorption capacity was found to shoot up to the level of 205.87 mg g −1 at 10 cm bed height, 100 mg L −1 feed concentration and 20 mL min −1 flow rate. Kinetic study done at regular intervals of time revealed high percentage removal of lead (99–96%) throughout entire span of reactor operation. Experimental data were well interpreted by Thomas model and Yoon-Nelson model. The reactor bed was regenerated after each adsorption and loaded metal was recovered up to the extent of ∼96%. The column reactor was efficient enough to treat lead containing actual industrial effluents.